ANALYSIS OF SALIVARY PH DIFFERENCES AFTER CHEWING XYLITOL GUM AND APPLYING CASEIN PHOSPHOPEPTIDE-AMORPHOUS CALCIUM PHOSPHATE (CPP-ACP) IN GRADE VIII STUDENTS OF SMPN 17 TASIKMALAYA CITY - Pujianti, Anita (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
ABSTRACTProblem statement: The prevalence of dental and oral health problems in Indonesia in adolescents aged 10-14 years is 55.6% and the prevalence of caries in children aged 10-14 years is 73.4%. Adolescents are categorized as quite susceptible to dental caries. One way to prevent dental and oral disease is by chewing xylitol gum and applying Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP – ACP). Xylitol cannot be metabolized by Streptococeus mutans and the application ofCasein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) can inhibit the demineralization process in teeth so as to prevent caries. Purpose: This study aims to determine how the pH of saliva compares after chewing xylitol gum and applying Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) in class VIII students at SMPN 17 Tasikmalaya City. Method: this study used pre-experimental method (quasi experiment, with non-equivalent design one group pre-test and post-test) research design as many as 61 students. The measuring instrument of the study uses universal indicators. Data analysis using Wilcoxon and Mann-Whitney tests. Results: based on statistical test results before and after chewing xylitol gum intervention, salivary pH was obtained from 6.19 to 6.74, Wilcoxon test results obtained p-value 0.017 and after CPP-ACP smearing intervention, salivary pH results were obtained 6.74 to 7.00 Wilcoxon test results obtained values p value 0.006. The results of the mann-whitney statistical test obtained a p-value of 0.015. Conclusion: There was a difference in salivary pH after chewing xylitol gum and applying Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP-ACP) in grade VIII students of SMPN 17 Tasikmalaya city.